A Cell-free Expression Pipeline for the Generation and Functional Characterization of Nanobodies - Haueis, Lisa; Stech, Marlitt; Kubick, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Cell-free systems are well-established platforms for the rapid synthesis, screening, engineering and modification of all kinds of recombinant proteins ranging from membrane proteins to soluble proteins, enzymes and even toxins. Also within the antibody field the cell-free technology has gained considerable attention with respect to the clinical research pipeline including antibody discovery and production. Besides the classical full length monoclonal antibodies (mAbs), so-called “nanobodies” (Nbs) have come into focus. A Nb is the smallest naturally-derived functional antibody fragment known and represents the variable domain (VHH, ~15 kDa) of a camelid heavy-chain-only antibody (HCAb). Based on their nanoscale and their special structure, Nbs display striking advantages concerning their production, but also their characteristics as binders, such as high stability, diversity, improved tissue penetration and reaching of cavity-like epitopes. The classical way to produce Nbs depends on the use of living cells as production host. Though cell-based production is well-established, it is still time-consuming, laborious and hardly amenable for high-throughput applications. Here, we present new data concerning the cell-free synthesis and functional analysis of relevant Nbs in a standardized mammalian cell-free system based on Chinese hamster ovary (CHO) cell lysates. Cell-free reactions were shown to be time-efficient and easy-to-handle allowing for the “on demand” synthesis of Nbs. Taken together, we complement the set-up of available methods and demonstrate a valuable new system for Nb selection and validation.